…Comic Books, Möbius Strips, Philosophy and… - Ian Hornsby (The Comics Grid: Journal of Comics Scholarship, 2019)
This article examines three comic books, Silver Surfer #11 (Marvel Comics), Omega Men #9 (DC Comics) and Promethea #12 (Americas Best Comics), as philosophy in themselves, and not merely as supplements to philosophical texts or as a convenient form through which the complex ideas of philosophy can be elucidated. Each of these three issues utilises the form of the Möbius Strip in their fabrication in a variety of ways that contend with concepts of the One and the Infinite. Within their construction, these comics challenge ways of reading that are exclusive to the form of the comic book medium and enable a distinctive method for exploring themes of the good life, truth, and creativity. The article then returns full circle once again to further interrogate the manner in which each of these three comic books engages with the four choices we are faced with in our understanding of the One and the Infinite.